Clinical Causes of Inflammation in Peritoneal Dialysis Patients - Yeoungjee Cho; Carmel M. Hawley; David W. Johnson (International Journal of Nephrology)
Inflammation at both systemic and local intraperitoneal levels commonly affects peritoneal dialysis (PD) patients. Interest in inflammatory markers as targets of therapeutic intervention has been considerable as they are recognised as predictors of poor clinical outcomes. However, prior to embarking on strategies to reduce inflammatory burden, it is of paramount importance to define the underlying processes that drive the chronic active inflammatory status. The present review aims to comprehensively describe clinical causes of inflammation in PD patients to which potential future strategies may be targeted.